2012
DOI: 10.1093/hmg/dds431
|View full text |Cite
|
Sign up to set email alerts
|

Kinase inhibitors arrest neurodegeneration in cell and C. elegans models of LRRK2 toxicity

Abstract: Mutations in leucine-rich repeat kinase 2 (LRRK2) are the most frequent known cause of late-onset Parkinson's disease (PD). To explore the therapeutic potential of small molecules targeting the LRRK2 kinase domain, we characterized two LRRK2 kinase inhibitors, TTT-3002 and LRRK2-IN1, for their effects against LRRK2 activity in vitro and in Caenorhabditis elegans models of LRRK2-linked neurodegeneration. TTT-3002 and LRRK2-IN1 potently inhibited in vitro kinase activity of LRRK2 wild-type and mutant proteins, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 36 publications
1
63
0
Order By: Relevance
“…29 To determine whether TTT-3002 targets FLT3 kinase activity and inhibits autophosphorylation, we studied the effect of TTT-3002 treatment on the FLT3/ITD-expressing human leukemia cell lines Molm14 and MV4-11. Cells were subjected to 1 hour of treatment with increasing concentrations of TTT-3002 or AC220, previously the most potent published FLT3 TKI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…29 To determine whether TTT-3002 targets FLT3 kinase activity and inhibits autophosphorylation, we studied the effect of TTT-3002 treatment on the FLT3/ITD-expressing human leukemia cell lines Molm14 and MV4-11. Cells were subjected to 1 hour of treatment with increasing concentrations of TTT-3002 or AC220, previously the most potent published FLT3 TKI.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it may be a fairly selective FLT3 inhibitor under a realistic clinical dosing regimen. Indeed, when profiled against a panel of 140 kinases by Yao et al, 29 TTT-3002 has a rather high degree of selectivity in vitro. In our studies with TTT-3002, we observed an IC 90 of 1 nM against FLT3/ITD phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, overexpression of K1347A LRRK2, a GTP binding-deficient mutant with impaired kinase activity, did not induce dopaminergic neurodegeneration or behavioral deficits. Yao and coworkers have also demonstrated that pharmacological inhibition of LRRK2 kinase activity rescued dopaminergic neurodegeneration and dopamine-mediated behavioral deficits in worms overexpressing R1441C or G2019S LRRK2 (Yao et al 2013). These observations support a role for kinase activity as a critical mediator of neurotoxicity induced by R1441C and G2019S mutant LRRK2 in worm models.…”
Section: Caenorhabditis Elegansmentioning
confidence: 96%
“…Studies have also shown that LRRK2-IN-1 and other LRRK2 inhibitors mediate protection against LRRK2 toxicity in vivo. Specifically, both LRRK2-IN-1 and TTT-3002, another small molecule LRRK2-kinase inhibitor, were shown to protect dopaminergic neurons in C. elegans models of PD involving mutant LRRK2 expression [27] . This protection demonstrated the in vivo efficacy of small molecule kinase inhibitors against LRRK2 toxicity.…”
Section: Overview Of Parkinson's Disease and The Role Of Oxidative Stmentioning
confidence: 99%